2019
DOI: 10.1186/s12889-019-6842-x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and technological contributions of Latin America and Caribbean countries to the Zika virus outbreak

Abstract: Background The recent Zika virus (ZIKAV) epidemics disclosed a major public health threat and a scientific and technological (S&T) challenge. The lessons learned from the S&T response of Latin America and the Caribbean (LAC) countries are critical to inform further research and guide scientific investments. The present study aimed to assess how new S&T knowledge produced and disseminated regionally can contribute to address global health challenges. Methods Scientometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…The study showed that, besides the number of publications, the prominence of a given researcher in scientific networks can be explained by the diversity of partnerships and the establishment of connections with the pioneers in the field [11]. Also, a recent study on Zika-related publications and patents from a scientometric perspective highlighted the strategic role played by the Latin America and Caribbean research network in terms of addressing the science and technology (S&T) challenges related to the outbreak [12]. The debate raised by such scientometrics studies applied to Zika enriches the discussion about the influence and centrality of certain groups, researchers and even countries.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that, besides the number of publications, the prominence of a given researcher in scientific networks can be explained by the diversity of partnerships and the establishment of connections with the pioneers in the field [11]. Also, a recent study on Zika-related publications and patents from a scientometric perspective highlighted the strategic role played by the Latin America and Caribbean research network in terms of addressing the science and technology (S&T) challenges related to the outbreak [12]. The debate raised by such scientometrics studies applied to Zika enriches the discussion about the influence and centrality of certain groups, researchers and even countries.…”
Section: Introductionmentioning
confidence: 99%
“…Lacking adequate resources to compete with foreign investigators, local scientists were largely forced to concede attribution over authorships, not receiving commensurate credit for publications stemming often from their own previous work (Chinchilla-Rodríguez et al, 2018;Machado-Silva et al, 2019). For instance, while several South American institutions collaborated in Zika virus research, all the leading institutions for Zika-related patents are based in the United States, China, and France (Machado-Silva et al, 2019), Thus, this situation resulted in so-called "helicopter" practices-foreign-backed groups conducting massive, accelerated studies culminating in high-profile publications, then returning home without following through with real-world applications that would translate intellectual findings into local community aid (Nordling, 2018). We therefore call on developed nations, and funding agencies, to foster a healthy, reasonable degree of accountability and longterm engagement between foreign labs and local communities they work in.…”
Section: A Caveatmentioning
confidence: 99%
“…Scientometrics is an interdisciplinary science that uses mathematical and statistical methods to quantitatively analyze all knowledge carriers. It provides a reliable method for researchers to deeply understand the study in this field, including the analysis of different databases, such as Web of Science, 8 Pubmed, 9 Scopus, 10 Derwent, 11 etc. Among them, Web of Science is the most common, there is also analysis using different software, for instance: CiteSpace, 12 VOSviewer, 13 Histcite, 14 etc.…”
Section: Introductionmentioning
confidence: 99%